2021
DOI: 10.1158/1538-7445.am2021-ct125
|View full text |Cite
|
Sign up to set email alerts
|

Abstract CT125: Evaluation of potential drug-drug interactions (DDIs) between futibatinib and CYP3A inhibitors/inducers, CYP3A substrates, or proton pump inhibitors (PPIs)

Abstract: Background Futibatinib is an oral, irreversible FGFR1-4 inhibitor with clinical activity in cholangiocarcinoma and other FGFR-aberrant tumors. The recommended futibatinib dosage is 20 mg once daily (QD). In vitro studies have shown that futibatinib is predominantly metabolized by and inhibits cytochrome p450 3A (CYP3A); futibatinib is also a P-glycoprotein substrate. Two phase 1 studies were performed in healthy volunteers to evaluate potential DDIs between futibatinib and CYP3A substrates (midazolam; study 1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 0 publications
2
10
0
Order By: Relevance
“…Based on in vitro data that showed futibatinib inhibits and is primarily metabolized by cytochrome p450 (CYP) 3A and is a substrate of p‐glycoprotein (P‐gp), phase 1 studies were conducted in healthy subjects to assess the involvement of futibatinib in the CYP and P‐gp pathways 12 . Findings from these studies suggested that futibatinib was not expected to affect the metabolism of concomitant medications metabolized by CYP3A (eg, midazolam) 12 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Based on in vitro data that showed futibatinib inhibits and is primarily metabolized by cytochrome p450 (CYP) 3A and is a substrate of p‐glycoprotein (P‐gp), phase 1 studies were conducted in healthy subjects to assess the involvement of futibatinib in the CYP and P‐gp pathways 12 . Findings from these studies suggested that futibatinib was not expected to affect the metabolism of concomitant medications metabolized by CYP3A (eg, midazolam) 12 .…”
mentioning
confidence: 99%
“…Based on in vitro data that showed futibatinib inhibits and is primarily metabolized by cytochrome p450 (CYP) 3A and is a substrate of p‐glycoprotein (P‐gp), phase 1 studies were conducted in healthy subjects to assess the involvement of futibatinib in the CYP and P‐gp pathways 12 . Findings from these studies suggested that futibatinib was not expected to affect the metabolism of concomitant medications metabolized by CYP3A (eg, midazolam) 12 . However, strong CYP3A/P‐gp inhibitors and inducers (itraconazole and rifampin, respectively) significantly altered futibatinib plasma exposure: itraconazole increased futbatinib C max and AUC by approximately 51% and 41%, respectively, and rifampin decreased futibatinib C max and AUC by approximately 53% and 64%, respectively 12 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2 Similar PK outcomes were observed with futibatinib in phase 1 studies evaluating potential drug-drug interactions. 6 The safety profile of futibatinib in phase 1 and phase 2 studies in patients with advanced solid tumors was predictable and manageable [2][3][4] and similar to that of other FGFR inhibitors. [23][24][25][26] The most commonly reported AE with futibatinib was hyperphosphatemia.…”
Section: Discussionmentioning
confidence: 93%
“…Plasma futibatinib exposures with the 80-mg dose were expected to exceed those experienced at steady state in outlier patients receiving futibatinib 20 mg QD and under conditions of potential decreased elimination (eg, cytochrome P450 3A4 inhibition or hepatic impairment). 6 Cardiac safety is a major factor in drug development because some investigational agents can delay cardiac repolarization or prolong the heart-rate corrected QT (QTc) interval, potentially leading to life-threatening proarrhythmias such as torsades de pointes. 7 A number of cancer therapies, including tyrosine kinase inhibitors (TKIs), are associated with a prolongation of the QTc interval.…”
mentioning
confidence: 99%